2022
DOI: 10.1029/2022jd036871
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Relative Humidity and Particle Size on Chemical Aging of Tropical Peatland Burning Particles: Potential Influence of Phase State and Implications for Hygroscopic Property

Abstract: Peatland fires in Southeast Asia are an important source of primary organic aerosol (POA). Chemical aging of POA in the atmosphere produces oxygenated POA (OPOA). The OPOA production influences optical and hygroscopic properties, modulating the regional climate. However, the roles of environmental parameters such as relative humidity (RH) on chemical aging of peatland burning particles have rarely been investigated. Utilizing the potential aerosol mass (PAM) reactor, we conducted laboratory experiments for POA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…The experimental data were combined with annual average temperature and relative humidity (RH) data on the global scale, suggesting that the atmospheric lifetime of light-absorbing species in biomass burning OA depended on altitude due to variations in temperature and RH. Chen et al (2022) consistently demonstrated that oxidation of biomass burning POA was faster under high RH conditions. Influence of phase state of OA on atmospheric lifetime of POA has long been investigated (Knopf et al, 2005;J.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The experimental data were combined with annual average temperature and relative humidity (RH) data on the global scale, suggesting that the atmospheric lifetime of light-absorbing species in biomass burning OA depended on altitude due to variations in temperature and RH. Chen et al (2022) consistently demonstrated that oxidation of biomass burning POA was faster under high RH conditions. Influence of phase state of OA on atmospheric lifetime of POA has long been investigated (Knopf et al, 2005;J.…”
mentioning
confidence: 69%
“…Chen et al. (2022) consistently demonstrated that oxidation of biomass burning POA was faster under high RH conditions. Influence of phase state of OA on atmospheric lifetime of POA has long been investigated (Knopf et al., 2005; J. Li et al., 2020; J. Li & Knopf, 2021; Shiraiwa et al., 2011), yet it is still not sufficiently understood for accurately simulating in global models.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation